The curious incident of the franc in the Gambia: exchange rate instability and imperial monetary systems in the 1920s. (18th January 2016) - Gardner, Leigh
Abstract : In 1922, British colonial Gambia demonetized the French 5-franc coin, which had been legal tender at a fixed rate in the colony since 1843. Until World War I, this rate was close to the international rate under the gold standard. When the franc began to depreciate in 1918, however, a gap emerged between the Gambian rate and the international rate, prompting a rapid influx of the coins. The demonetization cost the colonial administration over a year's revenue, affecting the later development of the colony. The 1920s have long been a fruitful period for the study of monetary history owing to the instability of exchange rates during and after the war. This article extends the study of this period to examine the impact of these changes on dependent colonies in West Africa, highlighting the importance of local compromises and particularities in colonial monetary systems.